2018
DOI: 10.1186/s12879-017-2860-4
|View full text |Cite
|
Sign up to set email alerts
|

Different responses of weather factors on hand, foot and mouth disease in three different climate areas of Gansu, China

Abstract: BackgroundTo determine the linear and non-linear interacting relationships between weather factors and hand, foot and mouth disease (HFMD) in children in Gansu, China, and gain further traction as an early warning signal based on weather variability for HFMD transmission.MethodWeekly HFMD cases aged less than 15 and meteorological information from 2010 to 2014 in Jiuquan, Lanzhou and Tianshu, Gansu, China were collected. Generalized linear regression models (GLM) with Poisson link and classification and regres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
17
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 37 publications
3
17
0
Order By: Relevance
“…These results indicated that the transmissibility of HFMD is lower than influenza. Commonly, the reproduction number of influenza was 1.4-2.0 [17], and was 1.81 in Changsha City [18]. Therefore, the results of our study are reliable.…”
Section: Discussionsupporting
confidence: 61%
“…These results indicated that the transmissibility of HFMD is lower than influenza. Commonly, the reproduction number of influenza was 1.4-2.0 [17], and was 1.81 in Changsha City [18]. Therefore, the results of our study are reliable.…”
Section: Discussionsupporting
confidence: 61%
“…To date (May 2019), only one relevant paper was retrieved by searching "hfmd arid semi-arid" on Pubmed. Similar to other studies, the retrieved paper found that weather factor such as average temperature and relative humidity have significant effect on HFMD [21]. In general, the study on HFMD in arid and semi-arid regions is still limited, more research in such climates would potentially make the mechanism of HFMD transmission clearer under different climate conditions.…”
supporting
confidence: 79%
“…The results in this paper showed that with a 1°C increase in temperature, HFMD incidence increased by 9.21%. While in Gansu province with similar climate conditions, a 1°C increase in temperature resulted in HFMD increase of only 1.8% [21]. This discrepancy indicates that other factors, regardless of climate or socioeconomic, may have played a part in determining the final outcome of HFMD incidence.…”
Section: Discussionmentioning
confidence: 88%
“…However, a study of HFMD in Gansu, China, showed that the HFMD reached the peak in June [35]. The climate of the two places mentioned above differs markedly.…”
Section: Discussionmentioning
confidence: 99%